Ultrasound-guided transversus abdominis plane block versus caudal block for postoperative analgesia in children undergoing inguinal hernia surgery: A comparative study - Amit Kumar; Neelam Dogra; Anupama Gupta; Swati Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Ultrasound-guided (USG) transversus abdominis plane (TAP) block has emerged as a safe and effective regional anesthesia technique as it provides adequate postoperative pain relief for lower abdominal surgeries. Caudal block is a gold standard technique in pediatric surgeries. Our aim was to compare the duration of postoperative analgesia between TAP block and caudal block in children undergoing inguinal hernia surgeries. Material and Methods: In a prospective, randomized, controlled study, 112 children of age 2-8 years and ASA grade I and II, undergoing elective inguinal hernia surgery were randomly allocated into two groups: Group T (n = 56) received USG-guided TAP block with 0.5mL/kg of 0.2% ropivacaine and Group C (n = 56) received caudal block with 1mL/kg of 0.2% ropivacaine. The primary outcome variable was the duration of postoperative analgesia and the secondary outcome variables included variation in hemodynamic parameters and adverse effects, if any. Results: There was no significant difference in median of CHEOPS score till 5 postoperative hours, thereafter till 24 postoperative hours, significantly lower CHEOPS score were found in Group T. Mean duration of analgesia was 523.44 ± 61.30 min in Group T, whereas in Group C, it was 352.59 ± 32.54 min. No significant difference was observed in hemodynamic variations and adverse effects. Conclusion: TAP block and caudal block both are effective in providing postoperative analgesia in children undergoing inguinal herniotomy. USG-guided TAP block was found to be superior as it provided longer duration of analgesia and reduced rescue analgesic dose without any significant adverse effects as compared with caudal block after inguinal herniotomy.